Sustainable clean-up technologies for soils contaminated with multiple pollutants: Plant-microbe-pollutant and climate nexus - Tripathi, Vishal; Fraceto, Leonardo F. [UNESP]; Abhilash, P. C. (Elsevier, 2015)
Soil is a vital life supporting system of the Planet Earth. However, it has been estimated that around 25% the global soils are highly degraded and 44% are moderately degraded mainly due to the pollution of metals and metalloids, persistent organic pollutants, pesticides, radionuclides etc. Additionally, the pollution due to new and emerging pollutants such as antibiotics, disinfectants, flame retardants, nanoparticles etc pose an additional threat to the homeostasis of the soil system. Therefore, sustainable management of contaminated soils are essential for maintaining the ecosystem services. Though chemical and physical methods are widely pursued for the remediation of contaminated soils, phytotechnolgies (plant-based clean-up technologies) are outweighed and often preferred as a clean and carbon-neutral solution for the remediation and sustainable management of the contaminated soils. Apart from that, plant-based clean-up also provide phytoprodcuts such as biomass, biofuels and other industrially important chemicals for bio-based entrepreneurial activities during remediation. However, phytoremediation does not give desired results in soil contaminated with mixed/multiple pollutants. Furthermore, it is unclear that how changing climate will affect the plant-microbe interactions and pollutants behaviour in the soil system. Moreover, there is only limited information available on the plant-microbe-pollutants nexus under changing climate. Therefore, the present work is aimed to (i) address the difficulties in remediation of soils contaminated with multiple pollutants (ii) delineate the plant-microbe-pollutant and climate nexus and (iii) identify the key sustainability indicators for evaluating the remediated system.
Keywords: Carbon neutral; Climate change; Contaminated soils; Multiple pollutants; Phytoremediation; Plant-microbe-pollutant interactions; Sustainability indicators; Sustainable remediation